A cascading power sharing control for microgrid embedded with wind and solar generation. (March 2019) - Li, Yujun; Xu, Zhao; Xiong, Liansong; Song, Guobing; Zhang, Jianliang; Qi, Donglian; Yang, Hongming
Abstract: Traditionally, wind power and solar photovoltaic (PV) power generation is non-dispatchable and their normal operation relies on Maximum Power Point Tracking (MPPT) control. Therefore, it can be of highly disturbance to the system dispatch in particularly context of microgrids. To effectively fulfill dispatch command or market schedule, a novel cascading power sharing control (PSC) scheme is proposed to coordinate wind and solar PV power productions in microgrids while reducing the loss of renewable energy production involved. Considering different properties of wind and solar PV power generation systems, the discrepancies between dispatch command (market schedule) and actual renewable generation is firstly counterbalanced by adjusting wind power output via temperately storing or releasing kinetic energy of turbine rotors. Only when rotors of wind generator reach their limitations, should solar PVs begin to reduce their generation. The proposed PSC scheme is fully simulated in a microgrid with wind and solar PV, and the simulation results clearly indicate it can be more energy efficient than the traditional dispatch method while fulfilling the dispatch demand. Highlights: We focus on the power sharing control (PSC) in a microgrid with high penetration of renewables. Energy production of wind generation (WG) and solar PV power generation is analyzed during PSC. A novel cascading PSC scheme is proposed for fulfilling the dispatch order while reducing energy production loss. The rotational mass of WG can be fully utilized for storing excessive energy and then released back when system needed. The proposed scheme can be more energy-efficient than traditional one while fulfilling the dispatch demand.